Relations of Hedonic Hunger and Behavioral Change to Weight Loss Among Adults in a Behavioral Weight Loss Program Utilizing Meal-Replacement Products. (November 2013) - Theim, Kelly R.; Brown, Joshua D.; Juarascio, Adrienne S.; Malcolm, Robert R.; O'Neil, Patrick M.
Greater self-regulatory behavior usage is associated with greater weight loss within behavioral weight loss treatments. Hedonic hunger (i.e., susceptibility to environmental food cues) may impede successful behavior change and weight loss. Adult men and women ( N = 111, body mass index M ± SD = 35.89 ± 6.97 kg/m 2 ) were assessed before and after a 15-week lifestyle change weight loss program with a partial meal-replacement diet. From pre- to post-treatment, reported weight control behavior usage improved and hedonic hunger decreased, and these changes were inversely related. Individuals with higher hedonic hunger scores at baseline showed the greatest weight loss. Similarly, participants with lower baseline use of weight control behaviors lost more weight, and increased weight control behavior usage was associated with greater weight loss—particularly among individuals with low baseline hedonic hunger. Further study is warranted regarding the significance of hedonic hunger in weight loss treatments.